Evaluation of spectral line mixing models and the effects on high pressure radiative heat transfer calculations. (July 2023) - Ren, Tao; Han, Yongkang; Modest, Michael F.; Fateev, Alexander; Clausen, Sønnik
Highlights: Comprehensive reviews for the empirical spectral line-mixing models were conducted. Line-mixing models were evaluated with experimental spectral data. Benchmark test cases for high-pressure radiative transfer calculations were presented. Abstract: At higher pressures, the spectral lines in a gas spectrum can become more broadened and shifted due to collisional effects, leading to increased spectral line mixing. In the present study, we have reviewed different line mixing models for modeling the absorption spectra for three gases of CO2, CO, and H2 O and applied these models to simulate radiative spectra for pressures within approximately 5–100 bar. The simulated data were compared with the yet-published high-pressure spectral experimental data as well as experimental data published in the literature. It has been found that the empirical "pseudo-Lorentz" line shape model considering the line mixing effects shows the best performance for modeling high-pressure gas spectra for the tested conditions, which is easy to be implemented and relatively accurate, thus is recommended for high-pressure radiative heat transfer calculations in engineering applications. Based on the selected "pseudo-Lorentz" line mixing model, we have constructed a high-pressure absorption coefficients database for CO2, CO, and H2 O for pressure ranging from 1 bar to 80 bar. The newly generated database considering the spectral line mixing effects was tested for radiative heat transfer calculations, and the results were compared with the ones without considering the line mixing effects. The significance of ignoring the line mixing effects on radiative heat transfer calculations under different pressures was evaluated with one-dimensional radiative heat transfer benchmark cases. The high-pressure absorption coefficients database is available from the corresponding author upon request.